Box-Behnken design for optimizing the acid blue dye adsorption on flower wastes (2013)
In this paper we identified the best conditions for the removal of Acid Blue 9 dye (AB9) using ower wastes (FW) as an adsorbent were determined using a full factorial 23 and a Box-Behnken design for further optimization. Adsorbent dose (D), dye concentration (C) and contact time (t), were the assessed variables. The dye content was quantied by UV-Vis spectrometry. The statistical model presented an adequate adjustment coecient (R2 = 99,18%), allowing to achieve a removal of 98,5% with a dosage of 7,8 gL-1, dye concentration of 7,11 mgL-1 and contact time of 104 min. These results suggest that owers wastes are an alternative and potential adsorbent material for the treatment of dissolved acid dyes.